PENGEMBANGAN MEDIA KOMIK PADA MATERI INDONESIAKU KAYA BUDAYA TOPIK KEKAYAAN BUDAYA INDONESIA BERBANTU POWERPOINT DI SD NEGERI 101921 BERINGIN - Sari, Vira Cantika; Fitrah Dwi, Dara (Jurnal Multidisipliner Kapalamada, 2024)
This research aims to develop comic media assisted by powerpoint on the material of Indonesiaku Kaya Budaya, the topic of cultural wealth that is suitable for use in the learning process in grade IV of elementary school. This research is a type of development research using the ADDIE development model up to the evaluation stage. The instrument data is a questionnaire or questionnaire given to several material expert validators, language expert validators, media expert validators, and teacher response validators. Based on the validation results from the material expert validator, a score of 76 was obtained with the criteria of "Good". From the validation results of the language expert, a score of 80 was obtained with the criteria of "Good". From the validation results of the media expert, a score of 95 was obtained with the criteria of "Very Good". From the validation results of the teacher's response, a score of 97 was obtained with the criteria of "Very Good". The average assessment score from the four expert validators obtained a score of 87. According to the assessment score criteria, it can be said that the comic media assisted by powerpoint on the learning of social studies material of Indonesiaku kaya budaya, the topic of Indonesian cultural wealth that was developed is "Very Suitable" for use in the learning process.